Regulation on Unjustified Geoblocking: A Hardly-Existing Market Facing a Hardly-Existing Challenge? - Mazur, Joanna (Pécs journal of international and European law, 2019)
The article presents a hypothesis that the scope of the regulation on unjustified geoblocking and its provisions address the challenges which had been previously identified under the term geoblocking to only a very limited extent. It can be interpreted as the result of the semantic shift concerning what is understood as geoblocking, which can be observed in European Union documents, leading to the exclusion of copyright protected content from the scope of the regulation. The article shows this process and the consequences of adopting such a limited approach towards geographic dis- crimination within the digital single market for the provisions of the regulation on unjustified geo- blocking. Moreover, the article presents the alternative to the anti-geoblocking regulation, namely the provisions of the regulation on cross-border portability of online content services in the internal market. It shows how the concept of portability may actually create borders in the digital single market instead of removing them. The article concludes with a section which focuses on consid- ering whether a regulation on geoblocking might be perceived as a tool to combat hardly-existing obstacles to a hardly-existing European digital single market.